II International Scientific Theological Conference “Spiritual Silk Road. Creativity. Integration”, Bolgar–Kazan, 3–5 September, 2017 - L.S. Giniyatullina (Золотоордынское обозрение)
On September 3–5, 2017, the Second International Scientific Theological Conference “Spiritual Silk Road. Creativity. Integration” was held as a continuation of the official opening of the Bolgar Islamic Academy. The conference was organized by the Russian Mufties Council, the Spiritual Administration of Muslims of the Russian Federation, the strategic vision group “Russia – Islamic World”, Kazan Federal University. The grand opening of the Bolgar Islamic Academy was held on September 4 in the town of Bolgar (Republic of Tatarstan). The plenary session saw the presentation of the theological work “Qalandar-name” of the Golden Horde thinker and spiritual leader Abu Bakr Qalandar Rumi, translated from Farsi. Assistant to the President of Tatarstan Kamil Iskhakov was elected President of the Bolgar Islamic Academy. Deputy Mufti of the Republic of Tatarstan for Education, Rector of the Russian Islamic Institute Rafik Mukhametshin was appointed Rector of the Academy. President of the Republic of Tatarstan Rustam Minnikhanov opened the solemn ceremony and noted in his speech: “For many centuries, Bolgar was a place of concentration of eminent scholars-theologians. By opening in its heart an Islamic academy, we revive its former greatness. Last year, the first stone was laid in the foundation of the academy on the anniversary of the adoption of Islam. Today it welcomes the first students”. The conference was continued in the form of sectional sessions and discussion roundtables on September 5 in the city of Kazan. The conference facilitated the interaction of the spiritual departments and the relevant government departments of Russia, China and the countries of Central Asia and the Southern Caucasus. The resolution was approved following the results of the conference determining the main results of the conference and the main directions for further cooperation.